PENGARUH BEBAN KERJA DAN KEPEMIMPINAN TERHADAP STRES KERJA DAN KINERJA KARYAWAN COSTUMER SERVICE GRAPARI TELKOMSEL DI KOTA PEKANBARU - Suci Nabela Primasari; Sri Indarti; Susi Hendriani (Ikatan Sarjana Ekonomi Indonesia Cabang Pekanbaru, 2019)
The aim of the study is to acknowledge the influence of workload and leadership to work stress and their impact toward costumer service performance at Grapari Telkomsel Pekanbaru. The technique of collecting data uses questioner distributed to 120 costumer services at Grapari Telkomsel Pekanbaru. The obtained data were analyzed by using path analysis. Based on the data analysis, it can be concluded as the following; 1) There is a significant influence of workload on work stress. In one day costumer service had served nearly 50 customers, by establishment of queue SOP on the quantity of services it will decrease customer service workload. 2) There is a significant influence of leadership on work stress. This means that every effort made by the supervisor in managing his leadership will improve customer service performance. If the supervisor is more focused on the service sector before selling physical products, this will decrease customer service workload. 3) There is a significant influence of workload on performance. With the existence of effective workload management will be able to increase whole employee productivity as well, this is related to efficiency and effectiveness of solutions that produce high performance as output. 4) There is a significant influence of leadership on performance. With the existence of effective briefings by supervisors, they will be able to increase cooperation in discussing customer problems that occur most often so that overall employee performance increases. 5) There is a significant influence of work stress on performance. By managing the number of customer queues due to the absence of customer service, it will reduce the risk of customer service work errors and improve their performance. 6) There is a significant indirect effect between workload on performance through work stress. With the addition of SOP service time standard from 15 minutes into 20-25 minutes, this will reduce workload and improve customer service performance. 7) There is a significant indirect effect between leadership on performance through work stress. With the addition of customer service employee recruitment, it is expected to reduce overall job stress to be comparable and increase the ability to handle the number of customer every day.